Increasing incidence of colorectal cancer in young adults in Europe over the last 25 years - Vuik, Fanny Er; Nieuwenburg, Stella Av; Bardou, Marc; Lansdorp-Vogelaar, Iris; Dinis-Ribeiro, Mário; Bento, Maria J; Zadnik, Vesna; Pellisé, María; Esteban, Laura; Kaminski, Michal F; Suchanek, Stepan; Ngo, Ondřej; et al. (Gut, 2019)
OBJECTIVE: The incidence of colorectal cancer (CRC) declines among subjects aged 50 years and above. An opposite trend appears among younger adults. In Europe, data on CRC incidence among younger adults are lacking. We therefore aimed to analyse European trends in CRC incidence and mortality in subjects younger than 50 years. DESIGN: Data on age-related CRC incidence and mortality between 1990 and 2016 were retrieved from national and regional cancer registries. Trends were analysed by Joinpoint regression and expressed as annual percent change. RESULTS: We retrieved data on 143.7 million people aged 20-49 years from 20 European countries. Of them, 187 918 (0.13%) were diagnosed with CRC. On average, CRC incidence increased with 7.9% per year among subjects aged 20-29 years from 2004 to 2016. The increase in the age group of 30-39 years was 4.9% per year from 2005 to 2016, the increase in the age group of 40-49 years was 1.6% per year from 2004 to 2016. This increase started earliest in subjects aged 20-29 years, and 10-20 years later in those aged 30-39 and 40-49 years. This is consistent with an age-cohort phenomenon. Although in most European countries the CRC incidence had risen, some heterogeneity was found between countries. CRC mortality did not significantly change among the youngest adults, but decreased with 1.1%per year between 1990 and 2016 and 2.4% per year between 1990 and 2009 among those aged 30-39 years and 40-49 years, respectively. CONCLUSION: CRC incidence rises among young adults in Europe. The cause for this trend needs to be elucidated. Clinicians should be aware of this trend. If the trend continues, screening guidelines may need to be reconsidered.
Keywords: Male; epidemiology; Evropa; lidé středního věku; předpověď; retrospektivní studie; Europe; míra přežití; Humans; Middle Aged; Survival Rate; kolorektální nádory; mužské pohlaví; Female; colorectal cancer; následné studie; ženské pohlaví; Retrospective Studies; incidence; Follow-Up Studies; Colorectal Neoplasms; Incidence; Forecasting; mladý dospělý; Adult; Young Adult; dospělí; lidé; screening